A Contribution to the Knowledge of Composition and Classification of Holm Oak Forests in Istria - Baricevic, D.; Šapic, I. (Croatian Journal of Forest Engineering, 2011)
{{The forest vegetation of Istria is considered one of the most interesting vegetation types in the Republic of Croatia. This is confirmed by the presence of a large number of highly diverse forest communities occurring on the border between two completely different plant-geographical regions: theMediterranean region and the Euro-Sibe- rian – North American region. As climazonal vegetation, forests of holm oak in the Eu-Mediterranean represent special value and a particular asset. Owing to systematic research during the past fifty or more years, the general distribution of holm oak in Istria is well known; however, data on forest communities of holm oak and their phytocoenologcal characteristics are much less known. This means that until the present research, only about forty phytocoenological relevés of the forest stands of holm oak in Istria had been released, which clearly demonstrates that these stands have been insufficiently studied and that further detailed research is required. Synecological-veg- etation research was undertaken in 12 localities in the coastal part of Istria, startingwith the surroundings of Pore~ in the north-west, across the western and southern parts, to the surroundings of Pula (Fig. 1). Phytocoenological research of forest vegetationwas based on the principles of the Zurich-Montpellier School (Braun-Blanquet 1964). Our own phytocoenological relevés were entered into the Turboveg database (Hennekens and Schaminee 2001), to- gether with 30 published phytocoenological relevés of forests of holm oak and manna ash, taken in a broader re- search area and described as the subassociations typicum and cotinetosum. Atotal of 42 phytocoenological relevés were statistically processed. In addition to classical analysis, numerical analysis by means of SYN-TAX 2000 (Podani 2001) software was also conducted. Eco-indicator values according to Pignatti (2005) were applied to de- scribe the ecological conditions using the floral composition, while themean values for particular relevés and forest communities were calculated by means of the JUICE 6.3 programme (Tischy 2002). The applied cluster methods showed very similar results and the same general patterns. Accordingly, the ma- jority of the relevés are clearly divided into three groups, while only three relevés make up a separate group (Fig. 2). Further detailed analysis of the floral composition showed that the studied forest stands of holm oak belong to the first group of relevés, typical stands of holm oak andmanna ash to the second group, while stands of holm oak and manna ash with smoke tree (Table 1) belong to the third group, and so do the three separate relevés. The analysis also showed that all the analyzed phytocoenological relevés belong to the same association Fraxino orni-Quercetumilicis (Horvati} (1956) 1958, with all the floristic and ecological differences that indicate the affiliation to the three subassociations. Thus, the first group of relevés is represented by stands of holm oak andmanna ash with a signifi- cant amount of deciduous elements, the second group is represented by typical stands of holm oak andmanna ash, and the third includes stands in the form of maquis and less well developed forests, containing, apart from the spe- cies Cotinus coggygria, species of more open sites. This is presented in more detail in Table 1. Based on the comparisons of the floral composition in our own relevés with the stands of holm oak and manna ash in the Republic of Croatia described earlier, it can be concluded that our stands, in addition to the characteristic and differentiating species of the association Fraxino orni-Quercetum ilicis and the appertaining alliance, order and class, are strongly characterized by the elements from the neighbouring forests of pubescent oak with oriental horn- beam (Querco-Carpinetum orientalis Horvati} 1939). In the tree and shrub layers, these include the deciduous Quercus pubescens, Carpinus orientalis, Quercus cerris, Acer monspessulanum, Coronilla emerus ssp. emeroides, Ligustrum vulgare, Cornus mas, Ulmus minor, Sorbus domestica, Euonymus europaea and others, and in the ground layer the grasses Sesleria autumnalis, Carex halleriana, Brachypodium sylvaticum and Carex flacca. Such a large participation of these species, as well as the affiliation of our relevés to the association Fraxino orni-Quercetum ilicis, indicate the different nature and specific features that place it into a separate subassociation. Differences in the floral composition in relation to the subassociations typicum and cotinetosum can primarily be attributed to different synecological growth conditions, as seen from the analysis of ecoindicator values according to Pignatti (2005) (Table 2). The studied holm oak forests are characterized by the best synecological conditions and by species that indicatemore sciophylic, colder,more continental, more humid and richer sites than those of typical holm oak forests. It should be pointed out that, in relation to the previously described subassociation typicum, our phytocoenological relevés differ statistically in all ecological indicators, whereas in relation to the relevés of the subassociation cotinetosum, they differ inmost of the ecological indicators. These results confirm the earlier under- standing on the need to form a special, new subassociation within the forest of holm oak with manna ash. In order to make the final decision on the accurate nomination and systematic affiliation of the analyzed stands of holm oak, in addition to the conducted analyses, we should also take into account past descriptions of holm oak forests both from the area of Istria and from the entire distribution range of this species. As evident from all these works, only the subassociations typicum and cotinetosum are accompanied by phytocoenological relevés, whereas the others are only furnished with textual descriptions without any concrete phytocoenological relevés or a list of differentiating species. This prevented us from making a more accurate and better comparison and clear determination. However, taking into consideration the floral composition, the synecological conditions of its occurrence and past descriptions of the subassociations, variants and facies of the association Fraxino orni-Quercetum ilicis, it may be claimed that the studied stands belong to the subassociation carpinetosum orientalis subass. nova hoc loco. This is in accordance with the valid Code of Phytocoenological Nomenclature (see article 7). Hence, relevé 4 in Table 1 is taken as the nomenclatural type. Species Carpinus orientalis, Quercus pubescens, Acer monspessulanum, Ligustrumvulgare, Cornus mas, Celtis australis, Carex flacca i Carex halleriana have been determined as dif- ferentiating species. In order to reach the final solution to the problem of forests of holm oak with manna ash, both in Istria and in the overall distribution range of this community, we should conduct our own research over a broader area. By doing so we would obtain more comparable data and more specific conclusions on the systematic classifica- tion of this association into lower systematic units. Moreover, the newly studied sites provide an excellent basis for further monitoring of syndynamic processes in holm oak forests in Istria.
Keywords: carpinetosum orientalis; Classification; ecoindicator values; floral composition; Forests of holm oak; Fraxino orni-Quercetum ilicis; Istria